2019
DOI: 10.1002/jclp.22867
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and the psychological outcomes of trauma: A systematic review of quantitative studies

Abstract: Objective This is a broad review examining the relationships between religiosity and the psychological outcomes of trauma. Previous studies showed that some constructs of religiosity are associated with lower severity of symptoms of mental disorders, whereas others, for instance, negative religious coping, predict deteriorated mental health. Method A systematic review of peer‐reviewed quantitative studies was conducted to examine the patterns of relationships between religiosity and psychological outcomes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 114 publications
(188 reference statements)
2
22
0
Order By: Relevance
“…Consistent with prior studies, being affiliated with a religion was associated with PTG (Kucharska, 2020 ). It has been suggested that religious beliefs may provide a framework to facilitate more positive reappraisal of threatening situations (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with prior studies, being affiliated with a religion was associated with PTG (Kucharska, 2020 ). It has been suggested that religious beliefs may provide a framework to facilitate more positive reappraisal of threatening situations (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…There were no associations between posttraumatic growth and religious attitudes. The researchers point out that the detected relationships between religiosity and reaction to a traumatic event largely depend on the concept of religiosity adopted in the research and the type of trauma [ 41 ]. Perhaps if we measured positive religious coping, the centrality of religiosity or the frequency of religious practices in the lives of respondents, we would be able to discover such relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Previous gender-specific studies on this topic found an effect both among traumatized women (Florez, Allbaugh, Harris, Schwartz, & Kaslow, 2018 ) and among mostly male war veterans (Mihaljević, Aukst-Margetić, Vuksan-Ćusa, Koić, & Milošević, 2012 ). A recent systematic review of 79 quantitative studies did not find that religiosity affected trauma reactions, however (Kucharska, 2020 ). We have not found other comparable studies that have shown gender differences in alterations of systems of meaning or religious beliefs after trauma.…”
Section: Discussionmentioning
confidence: 99%